Creating an empirically-based model of social arts as a public health resource: Training, typology, and impact - Shefi, Noa; Orkibi, Hod; Huss, Ephrat (Frontiers in Public Health, 2022)
Introduction Mounting empirical evidence underscores the health benefits of the arts, as recently reported in a scoping review by the World Health Organization. The creative arts in particular are acknowledged to be a public health resource that can be beneficial for well-being and health. Within this broad context, and as a subfield of participatory arts, the term social arts (SA) specifically refers to an art made by socially engaged professionals (e.g., artists, creative arts therapists, social workers, etc.) with non-professionals who determine together the content and the final art product (in theater, visual arts, music, literature, etc.) with the aim to produce meaningful social changes. SA can enhance individual, community, and public health in times of sociopolitical instability and is an active field in Israel. However, SA is still an under-investigated field of study worldwide that is hard to characterize, typify, or evaluate. This paper presents a research protocol designed to examine a tripartite empirically-based model of SA that will cover a wide range of SA training programs, implementations, and impacts. The findings will help refine the definition of SA and inform practitioners, trainers, and researchers, as well as funding bodies and policymakers, on the content and impact of SA projects in Israel and beyond. Methods and analysis This 3-stage mixed methods study will be based on the collection of primary qualitative and arts-based data and secondary, complementary, quantitative data. Triangulation and member checking procedures will be conducted to strengthen the trustworthiness of the findings obtained from different stakeholders. Discussion Growing interest in the contribution of arts to individual and public health underscores the importance of creating an empirically grounded model for SA. The study was approved by the university ethics committee and is supported by the Israel Science Foundation. All participants will sign an informed consent form and will be guaranteed confidentiality and anonymity. Data collection will be conducted in the next 2 years (2022 to 2024). After data analysis, the findings will be disseminated via publications and conferences.